Developmental influences, muscle morphology, and sarcopenia in community-dwelling older men - Patel, H; Sayer, A; Jameson, K; Syddall, H; Martin, H; Cooper, C; Stewart, C (2012)
Background. Sarcopenia is associated with disability, morbidity, and mortality. Lower birth weight is associated with reduced muscle mass and strength in older people, suggesting that developmental influences are important in sarcopenia. However, underlying mechanisms are unknown. Our objective was to determine whether low birth weight is associated with altered skeletal muscle morphology in older men. Methods. Ninety-nine men with historical records of birth weight (≤3.18 kg and ≥3.63 kg), aged 68-76 years, consented for detailed characterization of muscle, including a biopsy of the vastus lateralis. Tissue was processed for immunohistochemical studies and analyzed to determine myofibre density, area, and score. Results. Muscle fibre score (fibres kilograms per square millimeter) was significantly reduced in those with lower birth weight: 1.5 × 10 vs 1.7 × 10 , p =. 04 unadjusted; p =. 09 adjusted for age, height, and physical activity. In addition, there was a trend for reduced myofibre density (fibres per square millimeter) in those with lower birth weight: total fibre density: 176 vs 184, type I myofibre density: 77 vs 80, and type II myofibre density: 99 vs 105. Types I and II myofibre areas (square micrometers) were larger in those with lower birth weight: type I: 4903 vs 4643 and type II: 4046 vs 3859. However, none of these differences were statistically significant. Conclusions. This is the first study showing that lower birth weight is associated with a significant decrease in muscle fibre score, suggesting that developmental influences on muscle morphology may explain the widely reported associations between lower birth weight and sarcopenia. However, the study may have been underpowered and did not include women supporting replication in larger cohorts of older men and women. © 2011 The Author.